(untitled) (Acta Scientiarum. Animal Sciences, 2025)
This study evaluated the effects of fertilizer levels, harvesting days and cropping years on the agronomic performance and nutritional value of Washo (Loudetia arundinacea) the grass. A 3´3*2 factorial arrangement in a randomized complete block design with three levels of nitrogen fertilizer (75, 100 and 120 Kg), three harvesting days (60, 90 and 120 days) and two cropping years was used. Data on number of tillers (TN), number of leaves (LN), leaf length (LL), plant height (PH), Leaf to stem ratio (LSR), herbage dry matter yield (HDMY), crude protein yield (CPY), nutritional composition, in vitro digestibility were recorded. The results indicated that significantly (p<0.01) higher values of PH (114.57 cm), LSR (0.76), LL (18.18 cm), HDMY (29.91 ton ha-1) and CPY (3.54 ton ha-1) at nitrogen fertilizer level of 100 Kg ha-1. Fertilizer levels and harvesting days revealed significantly different (p<0.001) results on dry matter (DM), crude protein (CP), ash, neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL) and in vitro dry matter digestibility (IVDMD) contents. Cropping years had also influenced (p<0.05) on PH, TN, HDMY, CPY, LSR, NT and LL of the grass. From dry matter yield perspectives, harvesting of Loudetia arundinacea grass at 120 days is recommended.